Stand der Radfahrausbildung an Schulen und motorische Voraussetzungen bei Kindern. Bericht zum Forschungsprojekt: FE 82.0366/2009. - Günther, Rudolf; Kraft, Martin (My University, 2015)
Die Radfahrausbildung (RA) im vierten Schuljahr ist der wichtigste Baustein der Verkehrssicherheitsarbeit in der Schule. Ihr Stellenwert entspricht der Bedeutung, die das Fahrrad für Kinder und Jugendliche zunächst als Spielgerät, dann zunehmend als Verkehrsmittel hat. Die Verkehrsteilnahme von Kindern hat sich in den letzten Jahren jedoch stark verändert, die eigenständige Mobilität hat abgenommen. Das Fahrrad stellt zwar weiterhin ein für Kinder aller Altersgruppen wichtiges Verkehrsmittel dar, Kinder haben jedoch insbesondere in den Städten immer weniger Gelegenheit, es eigenständig zu nutzen. Auch deshalb nehmen Kinder heute mit anderen motorischen Voraussetzungen an der schulischen Radfahrausbildung teil als früher. Im vorliegenden Forschungsprojekt war zu untersuchen, mit welchen Inhalten und Vorgehensweisen die heutige Radfahrerziehung in der Grundschule arbeitet.

Cycling proficiency training in the fourth academic year is the most important element in road safety work in schools. It has a status that equates to the significance that the bicycle has for children and adolescents - first as a toy and then increasingly as a means of transport. However, the way children interact with traffic has changed considerably in recent years, with a reduction in their independence of movement. The bicycle admittedly still represents an important means of transport for children of all ages, yet children, especially in urban areas have fewer and fewer opportunities to use one. Also for this reason more children with other motor skill needs take part in school-based cycling proficiency training today than previously. In this research project the content and processes used in today's cycling proficiency training in primary schools were examined. Furthermore we also sought to clarify how individual differences in children's achievement and weaknesses in mastering riding a bicycle can be measured empirically and which individual, social or physical parameters influence them above all else: the current state of research on this was discussed and formed the basis for planning the broad empirical surveys. On the basis of these findings, proposals are to be worked up concerning future cycling proficiency training in schools. In addition while cycling proficiency courses were running, police officers, teachers, parents and children (in total approximately 3,000) were given written questions and this was followed by a representative online poll carried out across Germany, involving 1,000 parents of children in the age range of 8-10 years old. In a further poll of police traffic instructors we looked for innovative models for promoting motor skills. From these, the responses of 17 police stations, the responsible class teachers, parents as well as children were examined in closer detail in a second phase of the main polling exercise. Four expert conferences were held and complementary interviews conducted nationwide to undertake a qualitative analysis of the processes involved in cycling proficiency training and for the development of proposals. The evaluation of the polling revealed that cycling proficiency training is still being carried across the whole country, as a rule with the work divided between schools and the police. However over the last few years there have been changes as far as the police are concerned. Inclusion is becoming increasingly important but in practical cycling proficiency training the limits are being reached, especially in traffic. Children's weaknesses regarding mobility skills when riding a bicycle which were discussed at length by all participants can be recorded quite precisely because of the large number of characteristic variables (appraisals of parents, self-assessments by the children, results from experimental short tests, school grades), where a whole panoply of different factors can be seen as causes. At any rate, this is an issue of greater importance for the police than for teaching staff, who recognize deficiencies in children's motor skills comparatively less often. Today multifaceted promotion of motor skills belongs to the school repertoire but it is often not comprehensive or continuous enough. In surroundings that restrict the children's experience of movement, intensive support in particular is increasingly on offer, something that the study verified. Almost all children have a child's bicycle (on average from the age of 3.6 years old), 50 per cent of children have previously played on a learner bike. Using a learner or balance bike has beneficial effects on motor skills. Approximately one child in six has no possibility to use a bicycle in or around the home. The majority of parents have practised bicycle riding with their child, most intensively between the ages of 4 and 7. A third of parents however have either not supported their child at all or only supported them a little. Because of the great importance of police collaboration, the authors recommend that this be maintained at all costs. In Federal States, where spending cuts cannot be avoided, efforts should be made beforehand to ensure the long-term success and quality of the training through discussions with all parties involved (schools, police, parents' representatives, outside sponsors). That notwithstanding, consideration should also be given to how parents themselves can provide greater support and be more closely involved. A certain basic level of support from the police is however in the view of the authors indispensable if the system is to remain viable. The potential for improvements can been seen in closer coordination and communication between all parties (nursery schools, schools, police, parents) in a more comprehensive promotion of motor skills as well as in teacher training. Parents should be informed as early as possible in the nursery schools (For example through the use of learner bikes) and be given clear advice as well as opportunities to practice, for example in the form of homework with an element of movement or on bicycle riding exercises.
Keywords: Kind; Bildung; Grundschule; Schule; Verkehrssicherheit; Radverkehrssicherheit; Verkehrserziehung; Unfallvermeidung